A Bidentate Resorcinarene‐Based Palladium Carbene Complex. Issue 13 (3rd April 2017) - Ngodwana, Lonwabo; Bose, Sritama; Smith, Vincent J.; van Otterlo, Willem A. L.; Arnott, Gareth E.
Abstract : The synthesis and characterization of a distally bridged, bidentate resorcinarene bis(carbene) palladium complex is described for the first time. Preliminary catalytic studies show promise for future developments along this framework. Abstract : A distally bridged, bidentate resorcinarene bis(carbene) palladium complex is synthesized and characterized for the first time. Preliminary catalytic studies show promise for future developments along this framework.